Research on security multi-party computing based on game theory - Xinglan ZHANG; Wei ZHENG (网络与信息安全学报)
In the classic millionaire agreement,one party can get the final wealth comparison results,you can not tell the other party,you can not comply with this agreement,combined with game theory can avoid this problem,you can make the participants away from the agreement proceeds less than compliance with the agreement,compliance with the agreement is the optimal strategy for the participant.At present,the problem of computational efficiency based on game theory is low,and the protocol greatly improves the computational efficiency by introducing a binary tree.